A practice-based approach to using acoustics and technology in musicianship training - Young,JF; Picinali,L; Moraitis,D (2007)
Digital audio tools can be used to facilitate many aspects of traditional note-based music making, but one of the challenges they present is also found in their potential to open up new opportunities for the shaping and deconstruction of sound in ways that are difficult to assimilate with traditional Western notation-based models of musical materials. Development of an understanding of the musical use of these new materials may require an expanded view of the nature of musicianship. This paper presents reflections on an attempt to address this by teaching musicianship via principles of acoustics and psychoacoustics in the context of a music technology undergraduate degree.